2015
DOI: 10.1159/000368812
|View full text |Cite
|
Sign up to set email alerts
|

Direct Spraying of Shakuyakukanzoto onto the Duodenal Papilla: A Novel Method for Preventing Pancreatitis following Endoscopic Retrograde Cholangiopancreatography

Abstract: Background/Aims: Topical epinephrine application to the duodenal papilla reduces spasm of the sphincter of Oddi and prevents acute pancreatitis following endoscopic retrograde cholangiopancreatography (ERCP). Shakuyakukanzoto (TJ-68) has an inhibitory effect on muscle contraction. Therefore, TJ-68 potentially allows the relaxation of the sphincter of Oddi, which can aid in the prevention of post-ERCP pancreatitis. Methods: Thirty-six patients planned for ERCP were divided into TJ-68 (n = 17) and control groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this study, we evaluated the efficacy of Shakuyakukanzoto administered directly into the duodenum immediately before ERCP. We have also found that Shakuyakukanzoto sprayed directly onto the duodenal papilla significantly reduced serum amylase concentration 1 h and 1 day after ERCP [40]. Although we assessed only ERCP, our findings might also apply to other endoscopic examinations, such as upper endoscopy, balloon endoscopy and colonoscopy.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we evaluated the efficacy of Shakuyakukanzoto administered directly into the duodenum immediately before ERCP. We have also found that Shakuyakukanzoto sprayed directly onto the duodenal papilla significantly reduced serum amylase concentration 1 h and 1 day after ERCP [40]. Although we assessed only ERCP, our findings might also apply to other endoscopic examinations, such as upper endoscopy, balloon endoscopy and colonoscopy.…”
Section: Discussionmentioning
confidence: 95%
“…SKT has been found to show immediate efficacy against painful muscle cramps induced by liver cirrhosis, hemodialysis, and diabetic neuropathy . SKT has been reported to inhibit acetylcholine‐induced and neurogenic contractions of the gastrointestinal tract and to decrease unfavorable smooth muscle contractions during upper and lower gastrointestinal endoscopy . SKT also inhibits oxytocin‐induced myometrial contractions of uterine tissue in pregnant women in a dose‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%
“…The same can also be applied to other preventive factors. Various drugs have been attempted to be sprayed onto the papilla including epinephrine until now 9,10 . However, their effects have not been proven yet.…”
mentioning
confidence: 99%